2019
DOI: 10.1002/dc.24148
|View full text |Cite
|
Sign up to set email alerts
|

Sclerosing mucoepidermoid carcinoma with eosinophilia of the thyroid: Case report of a rare lesion with novel genetic mutation

Abstract: Sclerosing mucoepidermoid carcinoma with eosinophilia (SMECE) is a rare primary cancer of the thyroid. This tumor is analogous to other primary tumors of the salivary glands, breast, pancreas, and esophagus. We present a case of this rare tumor with characteristic clinical features, ultrasound images, cytopathology, histopathology, and a heretofore undocumented somatic gene mutation. Additionally, we provide a succinct review of the controversial literature for this uncommon lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Reports on the cytological features of SMECE are very limited. [3][4][5][6][7] The FNAC findings of previous cases are summarised in Table 1…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reports on the cytological features of SMECE are very limited. [3][4][5][6][7] The FNAC findings of previous cases are summarised in Table 1…”
Section: Discussionmentioning
confidence: 99%
“…Primary SMECE of the thyroid is an extremely rare malignant neoplasm. Reports on the cytological features of SMECE are very limited 3‐7 . The FNAC findings of previous cases are summarised in Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BRAF V600E mutation was detected in two cases [110], and an APC gene variant of uncertain significance was also found in another case of SMECE [111]. Compared with conventional mucoepidermoid carcinomas, SMECEs are associated with more aggressive tumor biology.…”
Section: Sclerosing Mucoepidermoid Carcinoma With Eosinophiliamentioning
confidence: 94%
“…Sclerosing mucoepidermoid carcinoma with eosinophilia (SMECE) was first described as a distinct entity from mucoepidermoid carcinoma (MEC) in 1991 by Chan et al 1 Since that description, approximately 56 cases of SMECE have been reported with descriptions of histology 2 . Despite most thyroid nodules having been initially evaluated by fine‐needle aspiration (FNA), there are only 11 cases with descriptions of cytomorphology 3‐13 . No descriptions of SMECE have included concurrent salivary gland neoplasms.…”
Section: Introductionmentioning
confidence: 99%